Preferences for disease-related information and transitional skills among adolescents with congenital heart disease in the early transitional stage. (3rd October 2022) - De Hosson, M; Goossens, E; De Groote, K; Muino Mosquera, L; Wynendaele, H; De Backer, J
Abstract: Introduction and aims: The transition towards adult-focused healthcare comprises a complex process through which adolescents with congenital heart disease (CHD) should be carefully guided. Various task forces encourage implementing person-tailored transition programs, but detailed data on adolescents' preferences regarding disease-related information and acquirable transitional skills are mostly lacking. This study examined these preferences towards adolescents with moderately and severely complex CHD. Material and methods: A cross-sectional descriptive study including logistic regression analysis was performed in a Belgian tertiary CHD center with adolescents recruited from "Transition With a Heart" (TWAH). For this 4-year transition program, adolescents were invited to complete a communication paper (focused on the need for information) and an individualized transition plan (focused on the evaluation of transitional skills) prior to an outpatient visit. Only questionnaires completed in the early transition stage, from January 2016 to August 2021, were used for data analysis. Results: Forty-nine adolescents completed both questionnaires at an average age of 15.9±1.2 years. Of all adolescents, 59% indicated the need for information about the heart defect and surgical treatment, followed by 45% that expressed the need for information about sports and medication; and ≤27% regarding psychosocially-related topics. The proportion of girls needing information was larger than boys. Significantly more girls than boys requested information about surgeries (76% versus 46%; p=0.04). Younger adolescents were more likely to express a need for information about most topics and significantly more likely regarding surgeries (odds ratio=0.53; 95% CI [0.26 to 0.88]; p=0.03). A maximum of 14% of adolescents were interested in acquiring transitional skills. Larger proportions of adolescents perceived the relevant transitional skills as insufficient, from 21% to 83%. Conclusion: The preferences for disease-related information of adolescents with CHD are mainly related to medical topics and tend to decrease with increasing age. This motivates timely gauging of individual information needs and delivering disease-related information, ideally in the early teens. Furthermore, preferences varied according to gender, with more information requested by girls. Adolescents expressed minimal needs to acquire transitional skills despite the low self-perceived skills levels. This paradox requires further research to enable the adaptation of transition interventions. Funding Acknowledgement: Type of funding sources: None.